Left ventricular remodeling in mitral valve prolapse patients: implications of apical papillary muscle implantation. (13th July 2021) - Moura-Ferreira, S; Vandenberk, B; Masci, PG; Dresselaers, T; Garweg, C; Symons, R; Willems, R; Bogaert, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Mitral valve prolapse (MVP) causes left ventricle (LV) remodeling even in the absence of significant mitral regurgitation. PURPOSE: We sought to evaluate whether apical implantation of the papillary muscle (PM) has an influence on the pattern and severity of MVP-related LV remodeling. METHODS: All MVP patients who underwent Cardiovascular Magnetic Resonance at our institution between December 2008 and December 2019 were included, thoroughly reviewed and grouped according to apical/non-apical PM implantation. RESULTS: Apical PM implantation was found in 53/92 patients (58%) and associated with mitral leaflet thickening (p < 0.01) and a trend toward higher prevalence of mitral annular disjunction (p = 0.05). Whereas there were no differences between groups concerning ventricular volumes and ejection fraction, mitral valve prolapse location or severity of mitral valve insufficiency, patients with apical PM implantation showed more lateral wall remodeling with mid lateral wall thinning (2.1 [1.8-2.5]mm vs. 4.0 [3.5-5.0]mm, p < 0.01), increased LV eccentricity and a lower Global Circumferential Strain at this level (15 ± 3% vs. 20 ± 3%, p < 0.01). In long-axis direction, increased end-diastolic mid lateral wall angulation was found (i.e., angle <155° measured in the thinnest point of the mid lateral wall in 4-chamber view) with a higher angle variation during systole (25 ± 11° vs. 17 ± 8° p < 0.01). Remarkably, PM fibrosis was significantly more frequent in patients with apical PM implantation (i.e., 66% vs. 28%, p < 0.01). Importantly, PM fibrosis was observed in the apically implanted PM in the vast majority of cases (86%), showing a strong association between PM fibrosis and its apical implantation. Finally, a higher burden of premature ventricular complexes (>5%) and non-sustained ventricular tachyarrhythmias was found in patients with apical PM implantation: 53% vs. 25% (p = 0.04) and 38% vs. 18% (p = 0.04), respectively. CONCLUSIONS: Apical PM implantation is part of the phenotypic spectrum of MVP, significantly impacts LV remodeling and potentially may be related to increased ventricular arrhythmogenicity.